Rantak - the Traditional Watermill of Ladakh, India - HUSSAIN, A.; HUSSAIN, N. (Indian Journal of Hill Farming, 2015)
The present study was carried out in order to explore the knowledge about the indigenous machine used for the grinding of locally grown cereal crops and legumes of this remote mountainous region of India, i.e., Ladakh. Rantak, the traditional watermill of Ladakh driven by fast moving water, is used by the rural folk to grind wheat, barley, pea, etc. It is made from locally available materials by the local experts of village. Most of the mills become non functional during the harsh winter season of the region due to freezing of water as well as the turbine. This eco-friendly and safe structure in use since times immemorial has withstood the test of time.